A Study Of Anisotropic Dependent Toughening Mechanisms Of Cortical Bone Under Monotonic Loading - Shahrin, Siti Asiah Ismam (Universiti Sains Malaysia, 2021)
The fracture resistance of human cortical bone is adversely influenced by diseases such as osteoporosis that are age-related. Aging bones are prone to be porous in return making them easily exposed to bone fracture occurrence. Cortical bone toughening mechanisms are known to be dependent on its microstructure that is affected by cortical porosity considering void volumes within the cortical bone volume. There are abundant published works of literature that measure the relation between cortical bone and fracture toughness under Mode I loading via experimental procedures, however, simulation is, apparently on the contrary. The aim of this study is to investigate the relationship between the cortical bone microstructural properties and stress intensity factor, KI as the quantitative measure of bone fracture toughness. To address the subject mentioned, the bone is modelled as a compact tension (CT) specimen with crack size variations as also to investigate the toughness properties of the cortical bone concerning the crack size. Moreover, the motion of crack growth along its trajectory is also explored in highlighting the crack propagation in response to different cortical bone microstructures. The finite element analysis shows that the stress intensity factor increases as the number of microstructures and the crack size increase, besides, the presence of microstructure also does influence crack deflection as a matter of enhancing the cortical bone’s toughening mechanism, which is consistent with that reported in published literature.